A simple assessment tool for evaluation of cadaveric temporal bone dissection. (20th April 2017) - Mowry, Sarah E.; Woodson, Erika; Gubbels, Samuel; Carfrae, Matt; Hansen, Marlan R.
Abstract : Educational Objective: Objective metrics in skilled‐based educational courses allow trainees and instructors to assess performance and monitor progress. The objective is to validate a concise, easy‐to‐use instrument for assessment of resident skill during a timed cadaveric temporal‐bone (CTB) dissection. Study Design: Retrospective analysis. Methods: An instrument was developed to assess resident performance on a yearly timed microdissection of CTB. Five neurotologists participated in the assessment. Each reviewer's score was compared to the score given by the senior neurotologist each year for every resident. Spearman's correlation analysis was then used to assess the reproducibility of the instrument in assessing resident performance. The ability of the instrument to distinguish among experienced and novice trainees and to demonstrate improvement with experience were also assessed. Results: The instrument was created and used for 6 years. Thirty residents were assessed. Correlation of scores between the senior neurotologist and the other neurotologist together was very high ( r = 0.883, P < 0.001). Three specific tasks distinguished novice from senior dissectors: posterior canal, opening the membranous labyrinth, and disruption of the ossicular chain. Conclusion: A new instrument for assessment of resident skill on CTB dissection is presented. The instrument is easy to use, and scores derived from it are consistent across reviewers. The new instrument distinguishes experienced trainees from novice trainees, is sensitive to individual experience, and has proved useful in providing trainees with objective performance measures. Level of Evidence: NA. Laryngoscope, 128:451–455, 2018